Correction: Psychology and Neuroscience. The (New) Autonomy Question. - Bantegnie, Brice (Erkenntnis, 2026)
The article addresses corrections made to a previously published work, specifically noting missing references and inaccuracies in author names. It highlights the inclusion of two references: one by Brice Bantegnie on the distinctness question in psychology and neuroscience, and another by Adam J. Granger and Roger A. Nicoll regarding long-term potentiation mechanisms. Additionally, it corrects the author name from "David M. Kaplan" to "D.M. Kaplan" in specific citations. The publisher, Springer Nature, emphasizes its neutrality concerning jurisdictional claims in published materials.